Suppressive effects of the expectorant drug ambroxol hydrochloride on quartz-induced lung inflammation in F344 rats - Kanie, Shohei (J Toxicol Pathol, 2016)
Surfactant proteins (SPs) are essential to respiratory structure and function. The expectorant drug ambroxol hydrochloride is clinically prescribed to stimulate pulmonary surfactant and airway serous secretion. Therefore, ambroxol hydrochloride may affect SP production and pulmonary inflammation. Lung toxicity of fine particles of various materials has been examined previously in our in vivo bioassay using the intratracheal (i.t.) instillation approach. In the present study, we evaluated modulatory effects of ambroxol hydrochloride on quartz-induced lung inflammation in F344 rats. Male 6-week-old F344 rats were exposed by i.t. instillation to 2 mg of quartz particles suspended in 0.2 mL of saline. Ambroxol hydrochloride was administered at 0, 12, and 120 ppm in rat basal diet for 28 days, and then formalin-fixed paraffin-embedded lung, liver, and kidney samples were prepared. No changes in general condition, body and organ weights, or food consumption upon exposure to quartz were noted. The mean ambroxol intake in rats of the 12 ppm group was comparable to the human conventional dose. Histopathology of lung lesions was evaluated, and the degree of inflammation was scored. At 120 ppm, ambroxol hydrochloride significantly decreased individual lung inflammation scores for pulmonary edema and lymph follicle proliferation around the bronchiole, as well as the total inflammation score, in quartz-treated rats. Expression of SP-C in the type II alveolar cells and macrophages was greater in inflammatory lesions than in non-inflamed areas. Ambroxol treatment did not affect expression of SP-B and SP-C. In conclusion, we demonstrated that ambroxol hydrochloride relieves quartz-induced lung inflammation.